Journal of Badiou Studies 3 On Ethics (Punctum Books, 2014)
Journal of Badiou Studies (General Editors: Michael J. Kelly and Arthur James Rose) is a multilingual, peer-reviewed journal dedicated to the philosophy and thought of, and surrounding, the philosopher, playwright, novelist, and poet Alain Badiou. Badiou Studies is dedicated to original, critical and challenging arguments that directly engage with the conditions and circumstances of Badiou's thought. We aim to identify pertinent intellectual discourses, ideas, historiographies, and concepts, and seek articles that situate these theories within emerging events in politics, science, art and love. Badiou Studies is especially concerned with maintaining a fidelity to Badiou's thinking without collapsing into hagiography or celebrity fetishism. This is why we encourage works that actively critique Badiou's philosophy and his currency as an established philosophical figure. Badiou himself embraces this approach and serves on the journal's Advisory Board. Alain Badiou's small book on ethics (Ethics: An Essay on the Understanding of Evil) remains one of the most important points of entry into Badiou's thought, since it is not only widely read across disciplines but is also one of the most widely translated of all of his works. This issue of Badiou Studies (Vol. 3) draws together scholarly responses and criticisms to Badiou's ethics. Sometimes in agreement, sometimes in violent opposition, always faithful to the imperative to keep thought going.